Predictors of family-focused practices among mental health workers in Quebec - Piché, Geneviève; Villatte, Aude; Clément, Marie-Ève; Morin, Marie-Hélène; Maybery, Darryl; Reupert, Andrea; Richard-Devantoy, Stéphane; Fournier-Marceau, Marianne (Frontiers in Psychiatry, 2024)
Context. Engaging family members in the ongoing care of individuals with mental illness is a practice known to bolster the client's recovery journey and enhance the overall wellbeing of both children and families involved. Despite its potential benefits, there remains a dearth of understanding surrounding the implementation of family-focused practices (FFP) by mental health professionals serving adults, as well as the factors that could either promote or hinder such practices. This knowledge gap is particularly pronounced within North American settings.Goal. The goal of this study was to identify potential hindering and enabling factors of FFP used in adult mental health services.A sample of 512 professionals working with adult mental health clients, from all regions of Quebec, Canada, with a variety of disciplinary backgrounds and working in different work settings, completed the Family Focused Mental Health Practice Questionnaire (FFMHPQ). Multinominal logistic regression analysis was performed to assess the impact of several factorsorganizational, professional, and personalon the degree of family-based practices of mental health workers.Results and discussion. Findings of this study show that the strongest predictors for the adoption of higher FFP levels among adult mental health professionals in Quebec, are being employed on a full-time basis, perceiving a higher level of skills, knowledge, and confidence toward FFP, and having a supportive workplace environment. Results underscore the need to address both organizational and worker-related aspects to effectively promote better FFP in mental health services.